How is Kamishibai are able to Construct Students' Environment Literacy? - Irvan Permana; Annisa Nurramadhani; Najla Nurul Amalia (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2023)
The purpose of this study is to analyze how students' environmental literacy in STEM-based learning with Kamishibai learning media. The method that is used is Qualitative study. The location of this research is located in the Science Education study program at Pakuan University Postgraduate School, Bogor. The research subjects in this study were postgraduate students of the science education program. with a total of 20 students divided into 4 groups. Each group makes a kamishibai project by determining environmental problems first, then thinking about what is the best solution to overcome these environmental problems. The data that has been obtained will then be analyzed, processed using the RASCH Model and quantitative description. Environmental literacy will be analyzed based on indicators of each dimension of environmental literacy (competence, knowledge, and attitude). From this research is that students' environmental literacy tends to be good and in a positive direction, both in terms of their competence or knowledge related to the environment, as well as related to their attitudes towards the environment through learning using Kamishibai media and the STEM (Science, Technology, Engineering, and Mathematics) approach.